2021
DOI: 10.21037/tau-21-534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individualized psychological intervention on negative emotion and sleep quality of patients after bladder cancer surgery: a randomized controlled trial

Abstract: Background: Bladder surgery has a negative impact on patients' mental health, sleep quality. Conventional nursing interventions failed to meet the clinical needs. Therefore, this parallel-group RCT was performed to assess the effect of individualized psychological intervention on patients' negative emotions and sleep quality after bladder cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Since bladder cancer is significantly less common than breast or prostate cancer, no study is available so far that investigated pre-treatment sleep disturbances in patients irradiated for bladder cancer (1). Only one randomized study was found that analyzed the effect of individualized psychological intervention on post- operative sleep quality in patients undergoing surgery for bladder cancer (18). However, the prevalence of sleep problems was not stated.…”
Section: Discussionmentioning
confidence: 99%
“…Since bladder cancer is significantly less common than breast or prostate cancer, no study is available so far that investigated pre-treatment sleep disturbances in patients irradiated for bladder cancer (1). Only one randomized study was found that analyzed the effect of individualized psychological intervention on post- operative sleep quality in patients undergoing surgery for bladder cancer (18). However, the prevalence of sleep problems was not stated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing transurethral procedures are especially at a higher risk of developing CRBD and LUTS, which is widely acknowledged in the literature. [ 8 ] CRBD and postoperative LUTS have been shown to have a negative impact on the patients’ postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Negative psychological states, and their indirect influences on patient behavior (e.g., obesity, smoking, alcohol intake), may affect surgical recovery [17,19]. In particular, patients' psychological features may directly interact with the neuroendocrine and inflammatory pathways underlying the surgical stress response [17], with major repercussions on immunological perioperative state and surgical outcomes [20].…”
Section: Psychological Features and Perioperative Metabolic Adaptationmentioning
confidence: 99%